Pembuatan Gim Edukasi Sejarah Pertempuran Tiga Hari Surabaya Menggunakan Interactive Digital Narrative - Aditya Primayudha; Pratama Wirya Atmaja; Afina Lina Nurlaili (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
The rapid development of technology has impacted various aspects of life, including educational institutions, which are increasingly utilizing information technology to enhance the quality of learning. One significant advancement in information technology is the use of games as an educational tool. This research explores the Interactive Digital Narrative (IDN) design method in the development of history-based educational games. The game created in this study is set against the historical backdrop of the Pertempuran Tiga Hari Surabaya, which is one of the events leading up to the historic Pertempuran 10 November 1945 in Surabaya. Adapting a previously proposed methodology, the game is built using the Unity Game Engine and tested through Likert scale assessments. The test results reveal a positive average percentage of 80%, indicating that the IDN approach can make history-based educational games more engaging and effective. This research provides a valuable contribution to educational technology development, aiding educators in designing more efficient and meaningful lessons, particularly in the field of Social Sciences, which plays a crucial role in students' understanding of history and values like patriotism.